DETERMINANTS OF EMPLOYEE DEDICATION TO THE COMPANY AS A WHOLE - Indra Rustiawan; Abu Muna Almaududi Ausat; Silvy Sondari Gadzali; Suherlan Suherlan; Hizbul Khootimah Azzaakiyyah (Universitas Pahlawan Tuanku Tambusai, 2023)
One of the strengths of the company lies in the quality of human resources. The way an organization treats and values its employees will have an impact on how strong and competitive the organization is in facing challenges and competition. The purpose of this research is to analyze the main elements that are generally carried out consistently by large companies that make employees feel at home and fully dedicate their abilities to the organization. This research includes library research, because the research was conducted to search, analyze, make interpretations and generalizations from the facts of the results of thoughts and ideas written by business psychology experts. This research is descriptive qualitative with a secondary data analysis approach. This study found that employees will give full dedication if the company pays attention to several factors including respecting employee needs, developing responsibility as an effort to retain employees, internal training and development, and the ability to retain employees. This research is expected to enrich business psychology literature and become a reference for organizations when managing HR.